Involvement of homeobox transcription factor Mohawk in palatogenesis. (30th November 2021) - Adachi, Yuka; Higuchi, Aina; Wakai, Eri; Shiromizu, Takashi; Koiwa, Junko; Nishimura, Yuhei
Abstract: Palatogenesis is affected by many factors, including gene polymorphisms and exposure to toxic chemicals during sensitive developmental periods. Cleft palate is one of the most common congenital anomalies, and ongoing efforts to elucidate the molecular mechanisms underlying palatogenesis are providing useful insights to reduce the risk of this disorder. To identify novel potential regulators of palatogenesis, we analyzed public transcriptome datasets from a mouse model of cleft palate caused by selective deletion of transforming growth factor‐β (TGFβ) receptor type 2 in cranial neural crest cells. We identified the homeobox transcription factor Mohawk ( Mkx ) as a gene downregulated in the maxilla of TGFβ knockout mice compared with wild‐type mice. To examine the role of mkx in palatogenesis, we used CRISPR/Cas9 editing to generate zebrafish with impaired expression of mkxa and mkxb, the zebrafish homologs of Mkx . We found that mkx crispants expressed reduced levels of gli1, a critical transcription factor in the Sonic hedgehog (SHH) signaling pathway that plays an important role in the regulation of palatogenesis. Furthermore, we found that mkxa −/− zebrafish were more susceptible than mkxa +/+ zebrafish to the deleterious effects of cyclopamine, an inhibitor of SHH signaling, on upper jaw development. These results suggest that Mkx may be involved in palatogenesis regulated by TGFβ and SHH signaling, and that impairment in Mkx function may be related to the etiology of cleft palate.